Repair of Double-Strand Breaks by Homologous Recombination in Mismatch Repair-Defective Mammalian Cells - Elliott, Beth (American Society for Microbiology, 2001)
Chromosomal double-strand breaks (DSBs) stimulate homologous recombination by several orders of magnitude in mammalian cells, including murine embryonic stem (ES) cells, but the efficiency of recombination decreases as the heterology between the repair substrates increases (B. Elliott, C. Richardson, J. Winderbaum, J. A. Nickoloff, and M. Jasin, Mol. Cell. Biol. 18:93–101, 1998). We have now examined homologous recombination in mismatch repair (MMR)-defective ES cells to investigate both the frequency of recombination and the outcome of events. Using cells with a targeted mutation in the msh2 gene, we found that the barrier to recombination between diverged substrates is relaxed for both gene targeting and intrachromosomal recombination. Thus, substrates with 1.5% divergence are 10-fold more likely to undergo DSB-promoted recombination in Msh2(−/−) cells than in wild-type cells. Although mutant cells can repair DSBs efficiently, examination of gene conversion tracts in recombinants demonstrates that they cannot efficiently correct mismatched heteroduplex DNA (hDNA) that is formed adjacent to the DSB. As a result, >20-fold more of the recombinants derived from mutant cells have uncorrected tracts compared with recombinants from wild-type cells. The results indicate that gene conversion repair of DSBs in mammalian cells frequently involves mismatch correction of hDNA rather than double-strand gap formation. In cells with MMR defects, therefore, aberrant recombinational repair may be an additional mechanism that contributes to genomic instability and possibly tumorigenesis.